2016
DOI: 10.1002/2016gl071094
|View full text |Cite
|
Sign up to set email alerts
|

Transport of solar wind plasma onto the lunar nightside surface

Abstract: We present first measurements of energetic neutral atoms that originate from solar wind plasma having interacted with the lunar nightside surface. We observe two distinct energetic neutral atom (ENA) distributions parallel to the terminator, the spectral shape, and the intensity of both of which indicate that the particles originate from the bulk solar wind flow. The first distribution modifies the dayside ENA flux to reach ∼6° into the nightside and is well explained by the kinetic temperature of the solar wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…We show that out of these reflected protons from the SPA, a certain fraction of them indeed reaches the nightside, and also, we quantified the flux and energy of such a population. Recent studies have shown that due to the interaction of protons in near wake region with the nightside lunar surface, energetic neutral atoms are produced (Vorburger et al, ), and that the nightside surface charging can be affected due to the emission of secondary electrons (Nishino et al, ). The plasma in the near wake region generate instabilities and significantly affect the electromagnetic environment of Moon (Nishino et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We show that out of these reflected protons from the SPA, a certain fraction of them indeed reaches the nightside, and also, we quantified the flux and energy of such a population. Recent studies have shown that due to the interaction of protons in near wake region with the nightside lunar surface, energetic neutral atoms are produced (Vorburger et al, ), and that the nightside surface charging can be affected due to the emission of secondary electrons (Nishino et al, ). The plasma in the near wake region generate instabilities and significantly affect the electromagnetic environment of Moon (Nishino et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The indirect transport include the entry of solar wind scattered from dayside lunar surface to the near wake region (Nishino, Fujimoto, et al, ; Wang et al, ) and also the solar wind scattered from Earth's bow shock (Nishino et al, ). Further, new population of protons is found in the near lunar wake whose source(s) is(are) yet to be identified (Dhanya et al, , ; Vorburger et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, ions in a supersonic flow do not have direct access to the near-Moon wake, though a variety of entry mechanisms are discussed (Nishino et al 2009a(Nishino et al , 2009b, Halekas et al 2014a). Thus, the nightside of the Moon is generally subject to much lower (but not completely zero) incident fluxes of ions and electrons compared with those on the dayside when the Moon, which is located in the solar wind and magnetosheath, as has been observed in energetic neutral atom reflection ratios (Vorburger et al 2016). The situation is more complicated in the terrestrial magnetotail, where both sunward and anti-sunward flows commonly exist (Troshichev et al 1999;Øieroset et al 2002).…”
Section: Lunar Space Environmentmentioning
confidence: 99%
“…The ions interact with and perturb the ambient solar wind flow (Fatemi et al, 2014;Harada et al, 2014;Halekas et al, 2012Halekas et al, , 2014Halekas et al, , 2017. The ions travel on cycloid trajectories that can bring them thousands of kilometers upstream of the Moon (Futaana et al, 2003;Holmström et al, 2010), or give them access to the lunar wake and the night side surface (Fatemi et al, 2014;Futaana et al, 2010;Nishino et al, 2009;Vorburger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%